Computer Based Financial Administration Management for Public Service Accountability - Cantika Beatrice Jami; Elya Prihartini; Baiq Meirda Sabtia; Dwinta Ayu Karwindy; Nadia Lestari; Restu Alpiansah (Jurnal Masyarakat Madani Indonesia, 2026)
Effective management of regional financial administration is a fundamental pillar of good governance in local government institutions. The Mataram City Regional Finance Agency (BKD) faces increasing demands for accuracy, accountability, and transparency in handling vast volumes of financial documents. This article documents an internship-based community engagement at BKD Mataram Secretariat from February 5 to March 6, 2026, wherein a Management student from Universitas Bumigora participated directly in administrative and financial data management activities. A participatory observation method was employed, involving hands-on engagement in Accountability Letter (SPJ) management, financial document archiving, SP2D and SPM verification, Coretax data processing using Microsoft Excel, General Cash Book (BKU) reconciliation, and Regional Government Information System (SIPD) data structuring. Results demonstrate that computer-based technology, particularly Microsoft Excel with SUMIF functions, substantially enhanced data processing efficiency and accuracy. Systematic archiving and rigorous document verification proved critical for administrative accountability in the public institution. The engagement contributed meaningfully to BKD’s operational capacity while equipping the intern with practical competencies in public financial management. A final performance score of 90/100 affirmed the quality and impact of the activities conducted.